Emotional and qualitative outcomes among patients with left and right hemisphere stroke - Stockbridge, Melissa D.; Vitti, Emilia; Faria, Andreia V.; Hillis, Argye E. (Frontiers in Neurology, 2022)
The differences in mental health outcomes of right and left hemisphere strokes are well studied; however, there is a long-standing controversy surrounding whether depression is associated with lateralization of stroke or not. In this investigation, we examined the effect of lesion location on post-stroke depression controlling for lesion size and hemiparesis in a longitudinal sample assessed at acute, subacute, and chronic timepoints. As a secondary aim, we further examined the effect of lesion location on self-reported difficulties across a wide array of domains. A series of 134 patients with left hemisphere strokes and 79 with right hemisphere strokes completed the Patient Health Questionnaire-9 and an inventory of post-stroke abilities at within acute, subacute, and chronic windows following stroke. When controlling for hemiparesis and overall lesion volume, we found no difference in depression between groups at any timepoint. Additional exploratory analyses provided a further look at differing challenges associated with depression in each group.